The Impact of Early Modern Textbooks on Sundanese Writing in the Nineteenth Century - Moriyama, Mikihiro (ASPENSI in Bandung, Indonesia, 2010)
ABSTRACT: Modern textbooks are only one line towards modernisation in Sundanese writing. There were other lines, namely the Islamic institutions, the development of Malay, colonial efforts to standardise the Sundanese language, and the establishment of schools. Modern Sundanese writing was the knot that tied them together. This article tries to elaborate the impact of early modern textbooks on Sundanese writing. One of the most interesting examples of how a traditional writing changed is the âdangdingâ, a type of poetry. A long narrative composed in âdangdingâ is called âwawacanâ, a genre loved by the people in the 19th century. âDangdingâ was admired in Sundanese aristocratic circles and pervaded the elite community. The Dutch saw âdangdingâ as the most original and valuable kind of Sundanese writing and thought it the best way to convey modern information and enlighten the people. Sundanese themselfves were to think that prose was more transparent and clear and even more pleasant to read than âdangdingâ, as textbooks were made in the new form of writing.KEY WORDS: Modern textbooks, Sundanese writing, âdangdingâ, âwawacanâ, and social changes.About the Author: Prof. Dr. Mikihiro Moriyama is a Professor of Indonesian Studies at the Department of Asian Studies, Faculty of Foreign Languages NU (Nanzan University), 18, Yamazato-cho, Syowa-ku, Nagoya 466-8673, Japan. For academic purposes, he can be reached at: moriyama@nanzan-u.ac.jpHow to cite this article? Moriyama, Mikihiro. (2010). âThe Impact of Early Modern Textbooks on Sundanese Writing in the Nineteenth Centuryâ in TAWARIKH: International Journal for Historical Studies, Vol.2(1) October, pp.1-22. Bandung, Indonesia: ASPENSI [Asosiasi Sarjana Pendidikan Sejarah Indonesia], ISSN 2085-0980. Chronicle of the article: Accepted (August 17, 2010); Revised (September 20, 2010); and Published (October 28, 2010).